Chinese Football – From a State-Led Past to a Digital Future. Issue 3 (3rd July 2022) - Cockayne, David; Chadwick, Simon; Sullivan, Jonathan
Abstract: Following the 2014 announcement of Xi Jingping's vision for China to create a domestic sport economy worth $800+ million by 2025, discussion has arisen around how this might be achieved, who the key players in this industry are, and what the broader geo-politic effects might be for China, and the rest of the World. Of particular focus has been the investment and efforts levied specifically toward football. This special issue brings together a selection of the more recent empirical and conceptual studies concerned with China and football. This initial paper is presented as a contextual precursor to the five papers representing our special issue. Collectively, these papers draw on a variety of methodologies, and consider debates around China and football from micro, meso and more macro perspectives. We believe the research presented in this issue provides a rich and diverse source of learning for researchers and practitioners interested in the nature and effect of China's footballing vision.